Significant Others’ Perception on the Nurse Level Immunization Skills - Jaime P. Gabriel; Angelito Estoesta Alvarado; Micah Alexis Javier Candelario; Jovie Yabes Casalamitao; Angelica Carl Mae Pedro Cauilan; Kate Winslet Garduque Clemente; Toni Grace Ross Darwin (Health Notions, 2022)
Immunization saves lives, avoids diseases, and lowers both direct and indirect medical expenditures. Vaccinations continue to protect people of all ages against additional diseases as new vaccines are created and tested. Vaccines also help to limit illness transmission among families, loved ones, and neighbors, resulting in healthier communities. Immunization protects future generations from illness transmission by preventing disease transfer from one generation to the next. Patient Satisfaction level is important to medical health care providers, ensuring that patients are satisfied with the efforts they put in. This study aims to determine the satisfaction level of patients receiving Expanded Program on Immunization (EPI) rendered by Nurse Deployment Program (NDP) nurse from the Rural Health Unit of Echague, Isabela. To achieve this, the researchers made used of descriptive method of research through the use of a survey questionnaire in gathering the data needed. The result showed in Immunization that NDP nurses setting a schedule for patients going to the RHU for the EPI, got the highest mean among the different items with an interpretation of “Very Satisfied”. RHU nurses instructing mothers to provide Paracetamol for PRN use got the lowest level of satisfaction from their patients with an interpretation of “Unsatisfied”. The result showed in surveillance and monitoring that Nurses being respectful and understanding got an interpretation of “Very Satisfied” and Other matters regarding the surveillance and monitoring of patient got an average rating with the exception of nurses suggesting plans for achieving the health goals of the patient with an interpretation of “Unsatisfied”. This study concluded that patients receiving Expanded Program on Immunization were “Satisfied” both in immunization and, in monitoring and surveillance of Nurse Deployment Program nurse from the Rural Health Unit of Echague, Isabela. This may conclude that further studies should be initiated to determine other possible variables that may be correlated.Keywords: expanded program immunization; immunization skills; nurse